Digital Text Comprehension: How to Keep it on Track with Self-Regulated Learning? - Nurjanah, Ratih Laily; Priatmojo, Arif Suryo; Wulandari, Armeita Rahma (Universitas Negeri Semarang, 2022)
The era of technology brings some changes including the involvement of technology in the classroom. Among of them are reading comprehension activities. With the existence of texts in the internet, digital reading becomes a new literacy form in the learning process. Guided activities are considered important to help students deal with digital reading well. This study aims to propose activities based on Self-Regulated Learning strategy to be integrated with digital reading to keep the activities on track. This is a case study involving survey design and in-depth interview. A questionnaire was distributed to lecturers to assess how they conduct their reading classes with digital reading inside. The results can be arranged into 3 phases; Forethought and Planning phase, Monitoring phase, and Self-Reflected phase. It is important to give students time limitation to help them set their goal of learning. The monitoring of the activities can be reported in form of blog entry or on digital classroom or learning management system developed by institutions. The selfreflection can be conducted by asking students to retell the text they have read, the difficulties found and how they overcome the problems in form of podcast entry. Having these activities will help students to get involved more in various forms of technologies assisting them in learning process. These activities highlight the importance of guidance and instructions given by lecturers despite the involvement of technology and independence in learning.